2003
DOI: 10.1128/mcb.23.13.4701-4712.2003
|View full text |Cite
|
Sign up to set email alerts
|

Nonredundant Role of Bax and Bak in Bid-Mediated Apoptosis

Abstract: Animal models suggest that Bax and Bak play an essential role in the implementation of apoptosis and as a result can hinder tumorigenesis. We analyzed the expression of these proteins in 50 human glioblastoma multiforme (GBM) tumors. We found that all the tumors expressed Bak, while three did not express Bax. In vitro, Bax-deficient GBM (BdGBM) exhibited an important resistance to various apoptogenic stimuli (e.g., UV, staurosporine, and doxorubicin) compared to the Bax-expressing GBM (BeGBM). Using an antisen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
100
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(115 citation statements)
references
References 45 publications
13
100
1
1
Order By: Relevance
“…apoptotic) GBM Bax ( þ ) cells. 17 Western blots analysis of proteins co-immunoprecipitated with TOM22 or Bax a showed that in resting cells TOM22 was associated with TOM40 and that it became associated with Bax a under apoptotic conditions (Figure 2c). On the other hand, Bcl-2 was co-immunoprecipitated with Bax in resting cells and in apoptotic cells (Figure 2c).…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…apoptotic) GBM Bax ( þ ) cells. 17 Western blots analysis of proteins co-immunoprecipitated with TOM22 or Bax a showed that in resting cells TOM22 was associated with TOM40 and that it became associated with Bax a under apoptotic conditions (Figure 2c). On the other hand, Bcl-2 was co-immunoprecipitated with Bax in resting cells and in apoptotic cells (Figure 2c).…”
Section: Resultsmentioning
confidence: 98%
“…Bax a, Bax a activated by a preincubation with truncated form of Bid (p13-tBid) 17 and Bax C, a variant, which corresponds to a deletion of the first 19 N-T amino acids of Bax a. 18 We also used constructs in which the RFP was fused to two putative mitochondrial targeting signals in Bax (i.e.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most studies addressing the impact of Bax and Bak on apoptosis sensitivity of cancer cells therefore suggest that both proteins are partially redundant. Nevertheless, recent evidence delineates that Bax and Bak exert also nonredundant activities Cartron et al, 2003;Gillissen et al, 2003;von Haefen et al, 2004;Wendt et al, 2005). At the molecular level, this may be reflected by the fact that Bax and Bak are differentially controlled by additional factors such as VDAC2 (Cheng et al, 2003;Chandra et al, 2005).…”
Section: Introductionmentioning
confidence: 99%